THE EFFECT OF OIL SPILLAGE ON CROP YIELD AND FARM INCOME IN DELTA STATE, NIGERIA - Inoni ODJUVWUEDERHIE EMMANUEL (Journal of Central European Agriculture, 2006)
Environmental degradation of the oil-rich Niger Delta region has been wanton and continuous with dire health, social and economic consequences for its peoples, for over three decades. Using a sample of 262 crop farmers drawn randomly from 10 communities and 5 LGAs in the oil producing agro-ecological zones of Delta State, the negative impact of oil spill on crop production was accentuated. Oil spill reduced crop yield, land productivity and greatly depressed farm income as a 10 percentage increase in oil spill reduced crop yield by 1.3 percent while farm income plummeted by 5 percent. In order to halt the continual degradation of the Niger Delta environment, the authors recommend the enactment and enforcement of stringent environmental laws to protect the area as well as the implementation of policies to reduce the crushing level of poverty and guarantee a better livelihood for the people.